Secularization Of Pura Besakih In Bali - Ida Bagus Subrahmaniam Saitya; I Komang Suastika Arimbawa (Jurnal Penelitian Agama Hindu, 2020)
Pura Besakih is the largest temple in Bali and as Pura Kahyangan Jagat. Pura Kahyangan Jagat is a place of worship for Ida Sang Hyang Widhi Wasa and all of His manifestations. Pura Kahyangan Jagat is a general temple, meaning that everyone can pray at the temple to ask for safety/mercy, welfare, and shade in the universe. Pura Pura Besakih as a tourist attraction has an impact on a shift in values ​​and meaning, at the beginning of its establishment, Pura Besakih was a sacred temple, full of religious-magical values, but seen from the use of Pura Besakih as a tourist attraction that has attracted foreign tourists to visit to Pura Besakih. The method used is a qualitative method with data collection techniques in the form of observation and literature. There has been a change in the views and mindsets of the community and local government to take advantage of the Hindu spiritual cultural heritage into the form of economic values. Pura Besakih as an element of the wealth of Hindu spiritual culture that is preserved and observed by the community is commercialized for tourism purposes by utilizing Pura Besakih as a tourist attraction. These problems have caused the sacred and religious values ​​of Pura Besakih to experience secularization. Global culture with its ideology of freedom, may not recognize the rules for menstruation (menstruation) or cuntaka because there are deaths (according to village regulations, kala, patra that apply in the local area) to enter temples due to customary rules / awig-awig, this can cause Hindus feel uncomfortable when praying in temples.